Development of a nitrogen prediction model for 320 tonne converter - C M. Yoon; C-H Eom; Y D. Jeon; K S. Kim (The Australasian Institute of Mining and Metallurgy, 2024)
The carbon neutrality continues to require reduction of carbon usage in ironmaking and steelmaking processes. Specially, it is expected that the hot metal ratio (HMR) in the steelmaking process should be reduced essentially. Unfortunately, the reduction of the HMR in converter can bring about poor environment for nitrogen removal from molten Fe. From this situation, nitrogen prediction model has been developed to understand the fundamental of behaviour of nitrogen and quantitatively interpret its content changes in the converter process. Thermodynamic and kinetic approaches were improved based on existing mathematical model and attempted to predict nitrogen content in realtime by combining process data. In present study, heat supply from the oxidation (mainly carbon and silicon) and CO evolution in the converter are considered, and scrap melting due to the heat transfer from the molten Fe to the solid scrap charged in the converter also be considered.